2022
DOI: 10.1093/nar/gkac190
|View full text |Cite
|
Sign up to set email alerts
|

Stitchr: stitching coding TCR nucleotide sequences from V/J/CDR3 information

Abstract: The study and manipulation of T cell receptors (TCRs) is central to multiple fields across basic and translational immunology research. Produced by V(D)J recombination, TCRs are often only recorded in the literature and data repositories as a combination of their V and J gene symbols, plus their hypervariable CDR3 amino acid sequence. However, numerous applications require full-length coding nucleotide sequences. Here we present Stitchr, a software tool developed to specifically address this limitation. Given … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 80 publications
0
12
0
Order By: Relevance
“…2E). Each AIR can be outputted in a full-length (Heather et al 2022) or CDR3 only format. Additionally, to facilitate further ML processing, the data is annotated with a binary matrix showing for every immune signal its presence in every receptor and, if so, the positions in the receptor sequence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2E). Each AIR can be outputted in a full-length (Heather et al 2022) or CDR3 only format. Additionally, to facilitate further ML processing, the data is annotated with a binary matrix showing for every immune signal its presence in every receptor and, if so, the positions in the receptor sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2: LIgO workflow for configuring AIRR-ML benchmarking datasets (A) For initialization, a user may define general simulation parameters, such as the type of AIR (BCR or TCR), receptor-or repertoire-based simulation, paired-or single-chain receptors, type of sequence alphabet -nucleotide (nt) or amino acid (aa), output format -full-length (Heather et al 2022) or CDR3 only. For the receptor-based simulation, a number of generated AIRs and a set of immune signals with their frequencies in the final dataset are defined.…”
Section: Simulation Approaches For Generating Biologically Relevant A...mentioning
confidence: 99%
“…It has been suggested that DN-D41 expresses the TCRδ1/TCRβ heterodimer at the cell surface ( 36 ). The full-length TCRδ1, TCRγ, and TCRβ sequences were assembled with stitchR software ( 55 ). The TCRγ sequence used was the example data provided by stitchR.…”
Section: Methodsmentioning
confidence: 99%
“…To obtain a full TCRαβ sequence, TCRs without V/J gene information were removed. We used the Stitchr tool to reconstruct the full TCRαβ amino acid sequence from available V(D)J genes and CDR3αβ [29]. TCRαβ sequences that could not be reconstructed were also excluded.…”
Section: Methodsmentioning
confidence: 99%